Study on the Substitution Effect of Property Tax on Land Finance—Analysis based on Shanghai and Chongqing Reform Pilots - Tan, Xiaomeng (Journal of Global Economy, Business and Finance, 2024)
This paper aims to study the substitution effect of property tax on land finance through the pilot property tax reform implemented in Shanghai and Chongqing. Based on the theoretical foundation of analysing the impact of property tax on land finance, this paper selects the annual panel data of 35 large and medium-sized cities published by the National Bureau of Statistics (NBS) from 2006 to 2017, and analyses the impact of the pilot property tax reform on the dependence on land finance in Chongqing and Shanghai and its extent. The findings show that the pilot effect of property tax reform in Shanghai is consistent with theoretical expectations, while the opposite is true for Chongqing; under a reasonable property tax system, the substitution effect of property tax reform on land finance gradually increases over time. In the conclusion, the paper puts forward relevant suggestions.